Ultrastructure of the molar enamel in representatives of the genus Ellobius (Rodentia) in the Pleistocene and Holocene of Ukraine - Leonid Rekovets; Vitalii Demeshkant (Theriologia Ukrainica)
New data on the enamel ultrastructure of molars of selected extinct and extant representatives of the genus Ellobius (Arvicolinae, Rodentia) from the Pleistocene of the south of Eastern Europea, mainly from the territory of Ukraine, are presented. Among the analysed species are the extinct Е. tiliguliensis, E. paleotalpinus, E. tarchankutensis, E. tauricus, and E. melitopoliensis, some extinct populations of Ellobius talpinus from the Late Pleistocene, as well as the extant E. talpinus and E. fuscocapillus. It was revealed that the enamel of molars of these species has the same structure as the enamel of Cricetidae and it belongs to three types described by Koenigswald (1980): radial, tangential, and lamellar. Radial enamel is the prevailing type in Ellobius, which is the initial form in the evolutionary process of other types. According to Kilic et al. [1997], radial enamel can also be divided into three groups (І, ІІ, and ІІІ) by the arrangement of the interprismatic matrix (IPM) and prismatic enamel (PE) in its structure. The first type is characterised by an almost linear arrangement of IPM and PE, whereas the second type is reticulate, and the third one is always located near the enamel-dentin junction (EDJ) and is connected to dentin, the matrix of enamel formation. It was shown that in the lineage of the subgenus Ellobius and in the formation of the species E. talpinus the second type of radial enamel predominated, whereas weakly expressed lamellar enamel of various levels of evolutionary development is present only on the tips of conids (primitive and progressive enamel). In contrast, in the lineage of the subgenus Bramus (= Afganomys) and the formation of the species E. fuscocapillus monotypic (according to the density of IPM and PE) first type radial enamel predominates and lamellar enamel is absent. This line of development by morphological characters has traditionally been considered as progressive evolution of the genus, although (as it turned out) it is characterised by a more primitive enamel structure (lack of lamellar enamel). As a result, we were able to further substantiate the phylogeny of the genus Ellobius with new data from the morphologocal analysis of molars and to outline the prospects for possible use of the enamel structure as a character in the taxonomy and phylogeny of species of Cricetidae.